SPATIO-TEMPORAL ASSESSMENT OF LAND USE/LAND COVER CHANGE AND ITS IMPLICATIONS ON DONGA RIVER BASIN, TARABA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Disturbances due to anthropogenic activities, especially Land use/ Land cover change; modifies runoff and sediment transport leading to adjustment in channel dimension. To this effect, the land use/land cover change of Donga River Basin was conducted with the aid of temporal satellite images of 1985, 2000 and 2020 downloaded from the United States Geological Survey (USGS) achieve. An unsupervised classification was carried out in ARCGIS 10.3 where seven classes were generated namely: built up area, cropland, forest, grassland, plantations, water body, woodland and bare surfaces. Descriptive statistics was further used to analyse the data. The analysis revealed that Built-Up Area, Cropland, Grassland, Woodland and Bare surfaces increased by +3.41, +12.37, +2.88, +3.05 and +3.75 respectively; while Forest, Plantation and Water Body decreased by -20.93, -2.47 and -2.1 respectively. The implications of such changes at basin scale are increase sediment generated during agricultural activities which are capable of entrainment by fluvial processes, siltation, flooding, cutoffs, narrowing of geomorphic threshold, loss of anchorage for bank materials making it prone to under cutting, bank collapse, channel widening and loss of life and properties. It was recommended that healthy agricultural practices should be encouraged so as to reduce the amount of sediments generated from farming activities especially on hill slopes. Overgrazing and annual bush burning should be check mated in order to reduce the effect of nutrient leaching and erosion of the top soil. There’s also need for land use plan that is in line with ecological principles of the study area.
Keywords: Drainage Basin; Land use/Land cover; Sediments; Agricultural Practices